(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
The digital transformation in the labor market has enabled individuals to work remotely from home, reshaping traditional employment structures. This study investigates the impact of remote work on the labor supply of married women in the regions of Sulawesi, Maluku, and Papua (SULAMPUA), utilizing data from the 2023 National Socioeconomic Survey (SUSENAS). Employing advanced econometric techniques to correct for selection bias, we isolate the causal effect of remote work on weekly working hours. While initial observations suggest that working from home increases women’s labor supply, a rigorous causal analysis reveals the opposite finding that remote work actually reduces formal working hours by approximately 10–15 hours per week. This finding indicates that without adequate support systems, remote work arrangements tend to blur the boundaries between professional and domestic activities, causing women to substitute formal employment time with increased household responsibilities. For public administration and policymakers, this study highlights that digital infrastructure expansion alone is insufficient to close the gender gap. Effective digital employment policies require a foundation of gender-responsive services, specifically accessible childcare and social protection, to prevent remote work from reinforcing traditional domestic inequalities.